Proceedings of the 12th Annual SIGCSE Conference on Innovation and Technology in Computer Science Education 2007
DOI: 10.1145/1268784.1268831
|View full text |Cite
|
Sign up to set email alerts
|

Successful students' strategies for getting unstuck

Abstract: Students often "get stuck" when trying to learn new computing concepts and skills. In this paper, we present and categorize strategies that successful students found helpful in getting unstuck. We found that the students reported using a broad range of strategies, and that these strategies fall into a number of recognizably different categories.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
20
0

Year Published

2009
2009
2021
2021

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 34 publications
(20 citation statements)
references
References 11 publications
0
20
0
Order By: Relevance
“…Seeking help from people, even via social networks, highlights the importance of the social learning theory. [6] study showed that students most commonly follow the social aspect despite the diverse strategies. Engagement in Pra1 positively correlates with engagement in Pra2.…”
Section: Co2mentioning
confidence: 96%
See 4 more Smart Citations
“…Seeking help from people, even via social networks, highlights the importance of the social learning theory. [6] study showed that students most commonly follow the social aspect despite the diverse strategies. Engagement in Pra1 positively correlates with engagement in Pra2.…”
Section: Co2mentioning
confidence: 96%
“…[3] noted that when programming students get stuck, they frequently search the textbook for solutions. [6] reported that their subjects read, looked information up on the Internet, and used tools. Subjects sought help from peers, their instructor, or other faculty members.…”
Section: Literature Reviewmentioning
confidence: 99%
See 3 more Smart Citations